DEVICE FOR DETERMINING THE MECHANICAL PROPERTIES OF ELASTOMER MATERIALS - E. P. Manak; N. M. Poloneichik; N. T. Minchenia (Приборы и методы измерений)
Developed the device for determining the physical and mechanical properties of elastomeric materials. In contrast to the well-known device that operates on the method of Shore, used to measure only the hardness of elastomeric materials, developed the device can measure not only hardness, but also the relative deformation of the samples made of elastomeric materials, as well as the ability of these materials to restore the original dimensions after deformation. The device has a simple design includes coaxial with the direction of the force transducer strain into an electrical signal that provides a sensitivity of at least 3 mV/μm.